Public knowledge about sporotrichosis: A surveillance and communication project in One Health in a brazilian urban setting (Research, Society and Development, 2026)
This study aimed to evaluate the population’s knowledge of sporotrichosis based on an experience report. Sporotrichosis is an increasingly important zoonosis in Brazilian urban areas, highlighting the epidemiological role of disease transmission from domestic cats to humans. Based on the One Health model, this study developed an extension exercise in health surveillance on sporotrichosis, carried out by Veterinary Medicine students, by assessing the population’s knowledge and the institutionalized health communication strategies in the municipality of Belo Horizonte (Minas Gerais). We conducted a descriptive-exploratory study, involving action research with analysis of institutional materials and the use of an online questionnaire in a convenience sample (n=86). The results indicated that the population had significant knowledge gaps, even with the wide availability of official information, and found a disparity between self-perceived knowledge and mastery of the fundamental aspects of the zoonosis. Institutional communication strategies and daily animal handling behavior related to the risk of transmission are also reported as having limitations. It is the opinion that extension methods provide applicable training tools for health surveillance qualifications and that veterinarians have a strategic mission regarding health communication and sporotrichosis control in urban areas, emphasizing the need for participatory and interdisciplinary initiatives and practices within the framework of One Health.